METHODS OF INTELLECTUAL ANALYSIS OF DATA IN ELECTRONIC DEPOSITORIES: GENETIC ALGORITHMS - Aseev, G. G. (Radio Electronics, Computer Science, Control, 2012)
One of the possible methods of data intellectual analysis in high-volume electronic depositories is presented – genetic algorithms and their modification.